Do Larger Pollinators Have Higher Pollination Efficiency for the Generalized Pollination Plant Hibiscus mutabilis? - Xiaoqing Shi; Bin Zheng; Xiaoli Liu; Fangwen Li; Zhangshun Zhu; Qiumei Quan; Yunxiang Li (Biology)
To understand the reproductive strategies of the typically introduced plant Hibiscus mutabilis and to compare the pollination efficiency of its different pollinators, we observed, measured, and recorded the flowering dynamics, floral traits, and visiting insects of H. mutabilis. Furthermore, we compared the body size, visitation rate, and pollination efficiency of the pollination insects of H. mutabilis. The results indicated that, despite exhibiting specialized moth pollination characteristics based on similarities in flower features to other moth-pollinated species, H. mutabilis actually presented a generalized pollination system. The nectar of H. mutabilis attracted a variety of insects to provide pollination services, a total of five flower visitors, one moth species (Macroglossum pyrrhosticta), and four bee species (Xylocopa appendiculata, Xylocopa dissimilis, Bombus breviceps, and Apis mellifera), were found to provide pollination services for H. mutabilis. The pollination efficiency of these pollinators was related to the parts of their body in contact with the stamens and stigmas of flowers. Although M. pyrrhosticta was larger in size and its visitation frequency in our field observations was higher, its pollination efficiency was lower. This was due to the small part of its body (proboscis) contacting the two sexual organs of H. mutabilis while visiting flowers, resulting in a low amount of pollen being transferred and deposited. In contrast, the bee pollinators’ proboscis was significantly shorter than that of M. pyrrhosticta, and it must enter the flower to suck the nectar that is hidden deeply inside the base of the flower. Therefore, the body parts of bee pollinators in contact with the two sexual organs of H. mutabilis were larger than M. pyrrhosticta in the process of visiting flowers, and the pollination efficiencies were significantly higher than those of M. pyrrhosticta. In addition, larger bee pollinators have higher pollination efficiency. As a result, H. mutabilis suffered from pollen limitation due to the pollination efficiencies of the moth pollinators in the introduced habitats, but it compensated by attracting more species of bee pollinators.